Behaviour based screening questions and potential donation loss using the "for the assessment of individualised risk" screening criteria: A Canadian perspective. Issue 5 (20th June 2022) - Caffrey, Niamh; Goldman, Mindy; Lewin, Antoine; Osmond, Lori; O'Brien, Sheila F.
Abstract: Background: To reduce the risk of HIV transmission through transfusion, gay, bisexual and other men who have sex with men (gbMSM) are deferred from donating blood in many countries for varying lengths of time after having sex with another man. In 2021, screening algorithms to identify high‐risk sexual behaviours using gender‐neutral criteria (i.e., without any question on MSM or time deferral for MSM) were implemented in the United Kingdom based on recommendations in a report from the FAIR (For the Assessment of Individualised Risk) steering group. Objectives: This study examines the potential donation loss expected with these criteria if implemented in Canada. Methods: Responses from blood donors regarding engagement in behaviours such as chemsex and anal sex with a new or multiple partners within 3 months of donation were collected using an on‐site paper questionnaire. Results: Applying the FAIR criteria resulted in donation loss of 1.0% (95% CI: 0.8% – 1.1%). Donation loss would be higher amongst younger donors aged 17–25 (2.0%, 95% CI: 1.6% – 2.3%). Overall, 20% of donors reported feeling uncomfortable answering study questions but only 2.0% said it would stop them from donating. Conclusion: Donation loss could be compensated by newly eligible gbMSM and with increased recruitment and encouraging donation from infrequent donors.